Oswaldella crassa Pena Cantero and Vervoort 1998 - Peña Cantero, A. L.; Vervoort, W. (Zenodo, 2004)
Oswaldella crassa Peña Cantero and Vervoort, 1998 Oswaldella crassa Peña Cantero and Vervoort, 1998: 33–35, figure 1; Peña Cantero and García Carrascosa, 1998: 178; 1999: 214; Peña Cantero and Marques, 1999: 85. Material examined . 6/428 , Three stem fragments up to 35 mm long. Remarks . The material of this species was previously described and figured by Peña Cantero and Vervoort (1998). Oswaldella crassa is characterized by the absence of nematotheca in the hydrocladial internodes, the presence of two axillary nematophores and one 'mamelon' on the cauline apophyses, the shape of the hydrotheca, situated on the middle of the hydrocladial internodes, the strong development of the perisarc, the absence of node between cauline apophyses and hydrocladia, and the absence of internodes in the stem (cf. table 1). Ecology and distribution . Oswaldella crassa is known only from the Bransfield Strait area, where it was collected at depths from 662 to 1120 m in January (Peña Cantero and Vervoort, 1998). : Published as part of Peña Cantero, A. L. & Vervoort, W., 2004, Species of Oswaldella Stechow, 1919 (Cnidaria: Hydrozoa: Kirchenpaueriidae) from US Antarctic expeditions, with the description of three new species, pp. 805-861 in Journal of Natural History 38 on page 822 : {"references": ["PEN \u0360 A CANTERO, A. L. and VERVOORT, W., 1998, On two new species of Oswaldella Stechow, 1919 (Cnidaria, Hydrozoa) from Bransfield Strait (Antarctica), Polar Biology, 20, 33 - 40.", "PEN \u0360 A CANTERO, A. L. and GARCIA CARRASCOSA, A. M., 1998, Oswaldella vervoorti spec. nov. (Cnidaria: Hydrozoa), a new benthic hydroid from the South Shetland Islands, Antarctica, Zoologische Verhandelingen, 232, 175 - 180.", "PEN \u0360 A CANTERO, A. L. and MARQUES, A. C., 1999, Phylogenetic analysis of the Antarctic genus Oswaldella Stechow, 1919 (Hydrozoa, Leptomedusae, Kirchenpaueriidae), Contributions to Zoology, 68, 83 - 93."]}